2015
DOI: 10.1063/1.4929953
|View full text |Cite
|
Sign up to set email alerts
|

Damage buildup in Ar-ion-irradiated 3C-SiC at elevated temperatures

Abstract: Above room temperature, the accumulation of radiation damage in 3C-SiC is strongly influenced by dynamic defect interaction processes and remains poorly understood. Here, we use a combination of ion channeling and transmission electron microscopy to study lattice disorder in 3C-SiC irradiated with 500 keV Ar ions in the temperature range of 25–250 °C. Results reveal sigmoidal damage buildup for all the temperatures studied. For 150 °C and below, the damage level monotonically increases with ion dose up to amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 33 publications
6
29
0
Order By: Relevance
“…Furthermore, in Ref. [19], a comprehensive analysis of RBS/Cderived depth profiles of disorder revealed anomalous features and pointed out to the crucial importance of radiation defect dynamics, as also confirmed in two other studies [20,21].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, in Ref. [19], a comprehensive analysis of RBS/Cderived depth profiles of disorder revealed anomalous features and pointed out to the crucial importance of radiation defect dynamics, as also confirmed in two other studies [20,21].…”
Section: Introductionsupporting
confidence: 62%
“…From an experimental standpoint, apart from reports focused on the specific case of He-ion-induced damage in SiC [17,18], one can cite systematic studies reported by Weber et al [8] as well as by some of the present authors [19]. In both of these studies [8,19], the level of damage was quantitatively determined by Rutherford backscattering spectrometry in channeling mode (RBS/C). Both works provided evidence that, even at moderate temperatures of 250 °C and below, 3C-SiC undergoes pronounced dynamic annealing involving enhanced defect recombination.…”
Section: Introductionmentioning
confidence: 94%
“…1(b). These observations are in agreement with results of our recent systematic study15 of the T -dependence of damage buildup in 3 C -SiC under 500 keV Ar ion bombardment.…”
Section: Resultssupporting
confidence: 93%
“…15) is the maximum saturation fraction of defect clusters in the lattice, h(x ) is the Heaviside step function [ h(x ) = 0 for x  < 0 and h(x ) = 1 for x  ≥ 0], Φ crit is the critical dose above which amorphization proceeds, and ξ amorph is the amorphization cross-section constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation